-5y-5(-6-2y)=0 ?

what’s -5y-5(-6-2y)=0?

2 Answers
Mar 1, 2018

y=-6

Explanation:

Simplify by distributing:

-5y+30+10y=0

Move like terms to one side:

-5y+10y=-30

=>5y=-30

=>y=-6

Mar 1, 2018

-6.

Explanation:

Start by distributing negative 5 (following the order of operations - we can't simplify in the parentheses here first, so we move onto multiplication/division from left to right first).

-5y-5(-6-2y) =0

= -5y+30+10y=0

Combine like terms that contain y.

= 5y+30=0

Subtract thirty to the other side:
= 5y=-30

Finally divide by 5:
y=-6